Experimental Analysis of Rotor-Bearing System for Fault Detection - Ghosarwade, S. M.; Sawant, P. J. (Asian Journal of Science and Applied Technology, 2016)
Rotating system is a main part in any industry. The design of such systems in modern engineering is towards lower weight operating at super critical speed for longer periods of time. In actual working condition, faults are unavoidable due to the error in manufacturing; faults may develop in the system due to the operating conditions such as heat generation, unbalance, wear, misalignment, looseness etc. In this study, dynamic behavior of rotor-bearing system is studied. This model mainly represents the driving unit at industrial machine applications. Disc at the model can be considered as gear or pulley, etc .at the transmission line. Experimental vibration analyses in vertical direction of the system are implemented. Vibration monitoring with Run up measurement analysis and Spectrum graphs are used to diagnose the excessive vibration source. It is seen that vibration at the rotor-bearing system not only one faults but also combination of several faults such as unbalance, wear, misalignment, looseness, etc. A non- destructive evaluation method for left & right bearing is used to diagnose the undue vibration source before it become critical.